Enhancing human resources and organizational capacity of higher education institutions to catalyze innovations in agriculture and rural development - Nampala, M. P. (African Journal of Rural Development (AFJRD), 2017)
This Issue of the African Journal of Rural Development (Volume 2, Issue 4) comprises ten articles featuring six broad themes. The themes include human capital development and associated innovative models for training and learning at higher education institutions in Africa; niche markets for smallholder farmers and end-users; dietary diversification for better nutrition; optimizing cropping systems; compensation for customary properties to facilitate public good; and, perception of target legatees on the delivery of agricultural extension services. These themes represent contemporary issues in the rural development context for which research solutions and innovations are needed which once taken to scale have potential to bring about change in communities. All the articles are authored by universitybased research teams and the recommendations there-in are an indication of the contribution of higher education institutions to desired development targets at global and national levels. The key messages in this collection are (a) the need for promoting innovative models in postgraduate training and research that promote through use of heutagogy, a reflective learning approach that will facilitate the production of well-prepared graduates to handle the complexities of agricultural and rural development contexts; and, (b) beyond training human capital, higher education institutions play a critical role in generating solutions that have potential to accelerate uptake of innovations in agriculture and rural development for the betterment of livelihoods to promote experiential learning as a means of training labour market-ready graduates, universities should ensures a blended approach with respect to pedagogical, andragogical and heutagogical approaches to teaching for life-long learning.
Keywords: Andragogy; Heutagogy; Human capital development; Pedagogy